Reflection on BIM Development Practices at the Pre-maturity - Ramanayaka, Chamil Erik; Venkatachalam, Senthilkumar (Elsevier, 2015)
This study contemplates prevailing BIM (Building Information Management) development practices at the pre-maturity. BIM stimuli set by developers have zero attention towards integrating qualitative features and induce pessimistic/optimistic information processing. Also, an archival analysis showed that the survey-based methodology, which is predominantly used to assess industry readiness, does not pay adequate attention towards externalities (procurement, policy, technical and organizational contexts) and hence is not comprehensive enough to lead BIM development towards viable strategies. The ‘contextual-reflection’ is used to describe the effect of externalities and their governing effect towards practitioners’ attitudes and state-level BIM strategies. A preliminary study done in South Africa substantiated these arguments. Integrating the findings with the Technology Adoption Model and BIM's Levels of Development, a conceptual framework is suggested to evaluate industry readiness in a holistic manner.